SAT0226 Gut Inflammation is Linked to Degree of Bone Marrow EDEMA in Sacroiliac Joints of Patients with Axial Spondyloarthritis. (23rd January 2014) - Van Praet, L.; Jans, L.; Van den Bosch, F.; Jacques, P.; Carron, P.; Cypers, H.; Varkas, G.; Elewaut, D.
Abstract : Background: It has been recognized for a long time that about 60% of all spondyloarthritis (SpA) patients show microscopic inflammatory gut lesions, a fraction of which evolves into Crohn's disease(1 ). Recently, this high prevalence of microscopic gut inflammation was confirmed in a patient cohort fulfilling the Assessment of SpondyloArthritis International Society (ASAS) criteria for axial and peripheral SpA (Gent Inflammatory Arthritis and spoNdylitis cohort - GIANT), and several risk factors for microscopic gut inflammation were identified(2 ). Magnetic Resonance Imaging (MRI) enables us to identify early in the disease course patients with non-radiographic axial SpA (nr-axSpA) by assessing bone marrow edema (BME) of the sacroiliac joints (SIJ). However, the correlation between the extent of BME and disease activity remains unclear. Objectives: This study was designed to assess the link between BME of the SIJ and gut inflammation. Furthermore, we have evaluated the correlation between BME and established disease activity parameters. Methods: The GIANT cohort is a prospective observational cohort in which patients diagnosed with axial and peripheral SpA according to the ASAS criteria are prospectively followed; at present 150 SpA patients have been included. Ileocolonoscopy was performed in 54 patients (28 men and 26 women), never being treated with TNF blockers. Two patients had a history of inflammatory bowel disease. Mean age was 33.9 years. Eighty percent of the patients were HLA-B27 positive. Bone marrow edema was assessed by the Spondyloarthritis research consortium of Canada (SPARCC) score(3 ) and linked to the presence of gut inflammation. Patients with total ankylosis of the SIJ were excluded from this analysis as they showed no BME. Results: A normal gut histology was found in 55.6% of all patients, 11.1% patients showed acute lesions and in 33.3% chronic lesions were found. SPARCC scores were significantly higher (median, [interquartile range]) in the group of patients showing gut inflammation (16.5 [23.6]) compared to those with normal histology (9.0 [15.4], p= 0.042). The degree of BME was most pronounced in patients with chronic lesions. SPARCC scores correlated moderately with C-reactive protein (CRP)(r=0.418, p=0.003), whereas no correlation with BASDAI or ASDAS was seen. Conclusions: Higher degrees of BME were observed in patients showing gut inflammation. There was a moderate correlation between the degree of BME and CRP. These data solidify a link between mucosal inflammation and the degree of sacroiliac joint inflammation in axial spondyloarthritis. References: Mielants H, Veys EM, Cuvelier C, et al. The evolution of spondylarthropathies in relation to gut histology. II. Histological aspects. J. Rheumatol. 1995;22(12):2273-8. Van Praet L, Van den Bosch FE, Jacques P, et al. Microscopic gut inflammation in axial spondyloarthritis: a multiparametric predictive model. Ann Rheum Dis 2012. Nov 8. [Epub ahead of print] Maksymowych WP, Inman RD, Salonen D, et al. Spondyloarthritis research consortium of Canada magnetic resonance Imaging index for assessment of sacroiliac joint inflammation in ankylosing spondylitis. Arthrit Rheum-Arthr 2005;53:703-709. Disclosure of Interest: None Declared